PARADOKS ANONIMITAS: FILSAFAT IDENTITAS DALAM NOVEL SURAT PANJANG KARYA DEWI KHARISMA MICHELLIA - Saifur Rohman (Faculty of Humanities, Jember University, 2013)
Novel Poetics Surat Panjang tentang Jarak Kita yang Jutaan Tahun Cahaya (2013) by Dewi Kharisma Michellia is composed with an autobiographical technique to counter Katrin Bandel’s view on sexuality identity for young writer. This work may be seen from a different perspective of discussing woman, a self narrating style, gender, feminism, deconstruction, or even brought further to phenomenology practice. The discussion shows that the self character is able to merge into a non-self discourse and identity into non-identity and thus, becomes anonimousKeywords: identity, Surat Panjang novel, self character